Enhanced Power Control Approach for Tie Converter Based AC-DC Micro grids (International Journal of Life Sciences Biotechnology and Pharma Sciences, 2022)
Current AC-DC microgrid power management solutions have a number of technical shortcomings.When it comes to controlling the voltage of interconnected microgrids, certain current control methods areestablished with the primary purpose of distributing electricity among interconnected microgrids based on theirloading circumstances, whereas others do not take this into account. The current systems, on the other hand, areunable to successfully pursue these objectives. In order to tackle these issues, an autonomous powermanagement strategy is proposed, which takes into account the DC microgrid's individual loading conditionbefore importing power from the associated AC microgrid. Controlling DC microgrid voltage with fewerconverters is possible with this method. Generators and tie-converters can be used with the proposed systembecause it is plug-and-play compatible. A variety of operating scenarios have been used to evaluate theeffectiveness of the proposed control scheme. Researchers found that the proposed strategy successfully andindependently controls the DC microgrid's power shortfall while maintaining increased voltage resiliency.